The Impact of Nanoparticle Adsorption on Transport and Wettability Alteration in Water-Wet Berea Sandstone: An Experimental Study - Li, Shidong; Torsæter, Ole; Lau, Hon Chung; Hadia, Nanji J.; Stubbs, Ludger P. (Frontiers in Physics, 2019)
Wettability alteration was proposed as one of the enhanced oil recovery (EOR) mechanisms for nanoparticle fluid (nanofluid) flooding. The effect of nanoparticle adsorption on wettability alteration was investigated by wettability index measurement of Berea sandstone core injected with nanofluids and by contact angle measurement of a glass surface treated with nanofluids. Nanoparticle adsorption was studied by single phase coreflooding with nanofluids in Berea sandstone. The adsorption isotherm and the impact of adsorption on the effective permeability were investigated by measuring the effluent nanoparticle concentration and differential pressure across the core. Results showed that hydrophilic nanoparticles (e.g. fumed silica) made the core slightly more water wet, and hydrophobic nanoparticles (e.g. silane modified fumed silica) delayed spontaneous imbibition but could not alter the original wettability. It was found that hydrophilic nanoparticles treatment reduced contact angle between oil and water by about 10 to 20 degree for a glass surface. Results also showed that different types of nanoparticle have different adsorption and desorption behavior and different ability to impair the permeability of Berea sandstones cores.